DEVICES USING WIND ENERGY - Alijanov Abbasbek Azizjon-ugli,; Gulomov Odiljon Dilshodbek ugli, (Лучшие интеллектуальные исследования, 2024)
Abstract. Wind energy is the most common clean form of renewable energy in the earth's crust. Wind turbines produce electricity by using the force of the wind to drive an electrical generator. The project includes both a gravity configuration like a Savonius wind turbine and a Darrieus wind turbine configuration. The Savonius wind rotor has many advantages over others, as its construction is simple and inexpensive. It is independent of wind direction and has good starting torque at low wind speeds